Molecular phylogeny and ethology of the Family Plagiostomidae (Platyhelminthes, Prolecithophora), with integrative description of a new species, Plagiostomum robusta A. Wang, sp. nov. - Wang, Yujia; Huang, Jiajie; Zhang, Yu; Wang, Antai (Frontiers in Marine Science, 2024)
The taxon Prolecithophora, which is closely related to the well-known clade Tricladida, is rarely studied, particularly in terms of molecular phylogeny and behavioral characteristics. In this study, we employed an integrative analysis of molecular phylogeny, histology, and ethology to describe a new marine species, Plagiostomum robusta A.Wang, sp. nov. of the order Prolecithophora. Additionally, we obtained its nearly complete mitogenome sequence with annotations of 12 protein-coding genes, two rRNA genes and 22 tRNA genes. P. robusta is characterized by several features, including a pair of short tentacles, a terminal mouth and a terminal gonopore, a large variable pharynx, two extended front ends of the intestine, paired testes located behind the ovaries and outside the vitellaria, a muscular and movable distal sac, and a long tubular penis surrounded by a sheath. The phylogenetic analysis, based on 18S rDNA and 28S rDNA, revealed that the new species formed a clade with six Plagiostomum flatworms, indicating a close kinship with Plagiostomum. Despite contradictions between the traditional morphological classification system and the results of molecular phylogenetics, we chose to assign the new species to Plagiostomum based on comprehensive considerations. Moreover, our study has provided more insights into the behavioral features of Plagiostomidae species, as we found that P. robusta fed on other flatworms and engaged in cannibalism, and unexpectedly it mated via hypodermic inpregnation. This study represents the first comprehensive description of the reproductive behavior of Plagiostomidae species, contributing to the more in-depth understanding of the biological characteristics of this group.